Healing of donor sites of connective tissue grafts harvested by the single incision technique. A randomized clinical trial evaluating the use of collagen hemostatic sponge with or without sutures (2020)
Background: The aim of this study was to evaluate the effect of suturing on the early wound healing of donor sites of subepithelial connective tissue grafts (SCTG), harvested by the single incision technique (SIT), following the application of a collagen sponge. Methods: Thirty-six patientswere randomized to receive a collagen spongewith or without sutures in the palatal donor sites following connective tissue grafting via the SIT. Outcome variables were early healing index (EHI) at 7, 14, and 30 days, self-reported pain using a visual analogue scale (VAS) recorded on the 0 to 100 scale at 7 and 14 days, and immediate and delayed bleeding. Results: No significant differences were found between groups at baseline. EHI index showed no differences between groups in all-time intervals. Eight subjects from suture group (SG) and 10 from no suture group (nSG) showed complete wound closure at day 14 (P >0.05) and at 30 days, complete closure was observed in 35 out of 36 patients. Four subjects from the SG and three from the nSG had immediate bleeding (P >0.05), while delayed bleeding was observed in two subjects from the SG and three from the nSG during the first week of healing (P >0.05). No differences were found in VAS scale between groups (SG, 36.2 ±} 24.8; nSG, 21.5 ±} 24.2, P >0.05). Conclusion: It can be concluded thatwhen a collagen sponge is placed in palatal donor areas of SCTG harvest by means of the SIT (incision length of ≈15 mm), sutured and non-sutured sites display similar earlywound healing outcomes and patient-reported outcomes.